Optimization Design of SNS Sensor Structural Parameters for Battery Expansion Monitoring - Xu, Shibo; Wang, Zhe; Yang, Hanrui; Jiao, Shengxi; Liu, Jien; Shang, Zhiyuan (Frontiers in Energy Research, 2021)
In this paper, a method to improve refractive index(RI) sensitivity of single-mode no-core single-mode fiber(SNS) sensor structure is addressed through optimization of geometric parameters of no-core fiber(NCF), which could be used to accurately measure the irreversible deformation of battery expansion state caused by temperature. From the perspective of temperature changing RI of the electrolyte solution, the impacts of diameter, length, waveband on the performance of fiber sensor have been discussed as RI measurement range is 1.340-1.390. After optimization, RI sensitivity can reach approximately 2252.7nm/RIU and 2037.3nm/RIU with the length of 6.55mm and 6.75mm when RI is from 1.380 to 1.390.